Evaluation of Pedestrian Walking Speed in Rail Transit Terminal - Kasehyani, Nur Hanis (International Journal of Integrated Engineering, 2019)
Current trend shows an exponential increase in rail traffic passenger volume, causing more attention must be paid to the crowd safety in rail transit terminal (RTT). In Malaysia, Kuala Lumpur Sentral Station (KLSS) is the largest transit terminal and as of 2017, the commuters at KLSS have reached 180,000. With this substantial number of commuters, walking might be difficult especially during peak hours. Hence, a better understanding of crowd dynamics is the key to plan and manage the pedestrians’ flow in RTT. One of important crowd attributes that crucial to be quantified specifically is walking speed. While walking speed has been studied in general, such analysis specific to RTT commuters is still lacking. In this contribution, the main objective is to evaluate the walking speed of the commuters in KLSS by considering different pedestrians walking categories, like normal walking, walking with luggage and walking while looking at the gadget in hand. Data gathering was conducted by video footage during peak hours (morning, afternoon and evening) for four consecutive days. Total of 26 videos with 10 minutes duration were recorded and each video was analyzed using Autodesk Maya (2016) software with Human Behavior Simulator (HBS) plug-in. As the preliminary findings, the average walking speed of 393 pedestrians was 1.4 m/s. The average walking speed for normal walking female pedestrians was 1.46 m/s (morning), 1.34 m/s (afternoon), and 1.36 m/s (evening) and for normal walking male pedestrians was 1.38 m/s (morning), 1.44 m/s (afternoon), and 1.39 m/s (evening). Meanwhile, the average walking speed of male walking with luggage was 1.24 m/s (morning), 1.38 m/s (afternoon) and 1.38 m/s (evening) and for female walking with luggage was 1.14 m/s (morning), 1.27 m/s (afternoon) and 1.38 m/s (evening). Furthermore, the average walking speed of male walking with gadget was 1.01 m/s (morning), 1.41 m/s (afternoon) and 1.40 m/s (evening) and for female walking with gadget was 1.04 m/s (morning), 1.38 m/s (afternoon) and 1.32 m/s (evening). Male walking speed is higher compare to female in all three categories with 1.4%, 5.6% and 2.4% different in average walking speed for normal walking, walking with luggage and walking with gadget, respectively.